Microstructures and Mechanical properties of AA-5754 and AA-6061 Aluminum alloys formed by Single Point Incremental Forming Process - Shamchi, Sahand Pourhassan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Single point incremental forming (SPIF) process is considered as a cost-effective method to fabricate sheet metals because there is no need for dedicated dies which are used in other conventional processes. Due to the capability of forming sheets on CNC machines, the flexibility of this process is high which allows the operator to modify the geometry of the product much easier than the other methods like stamping. This study is carried out to investigate the effects of different forming parameters on the mechanical properties and microstructures of formed parts. The effects of wall angle, feed rate, spindle speed and lubrication are explored on AA5754 and AA6061 Aluminium Alloys. Tensile tests and optical microscopy are used to observe the effects of each forming parameter on the properties of the final parts. The results show that the wall angle has a major effect on the strength of the formed part. By increasing the wall angle, the strength, average grain size and the chaining of second phase particles increase; however, the amount of elongation decreases in both materials. Also, by increasing the feed rate, the strength and average grain size increase, but it has almost no effect on the elongation of both materials. The spindle speed has the least effect on strength and average grain size of both materials, but a slight increment is observed on the elongation in AA5754. To examine the effect of lubricant, hydraulic oil and grease are used on the AA5754 Aluminium Alloy. The results demonstrate that the strength of the part increases with the use of grease instead of hydraulic oil. Additionally, the average grain size in the part formed by grease is greater than of that formed with hydraulic oil. From the results, the wall angle and the feed rate are the most significant parameters affecting both microstructure and mechanical properties in SPIF process. Keywords: Single Point Incremental Forming, Mechanical properties, Microstructures, Wall angle, Feed rate, Spindle speed, Lubricant, Tensile test, AA5754, AA6061

ÖZ: Tek noktalı artan şekillendirme işlemi, sacları üretmek için ucuz bir yöntem olarak kabul edilir, çünkü diğer geleneksel yöntemlerde kullanılan özel kalıplara gerek yoktur. CNC makinesi yardımıyla çalışan bu işlem, esnekliği yükseltmiştir, ürünün geometrisini pres gibi diğer yöntemlerden daha kolay değiştirebilir. Bu çalışma şekilli parçaların mekanik özelliklerini ve mikroyapılarını farklı yapan parametrelerin etkilerini araştırmak için yapılmıştır. Duvar açısı, ilerleme hızı, iş mili hızı ve yağlama etkisi, AA5754 ve AA6061 üzerinde incelenmiştir. Gerilme testleri, ve optik mikroskopi nihai parçaların özelliklerine etkisini görmek için kullanılmıştır. Sonuçlar duvar açısının, şekillendirilen parçanın gücü üzerinde büyük bir etkiye sahip olduğunu göstermektedir. Duvar açısını artırmak, ortalama tane büyüklüğü ve materyalin gücünü artırır, ancak uzama miktarı her iki malzemde azalır. Bununla birlikte, besleme hızı, parçanın gücü ve ortalama tane boyutu artmıştır, ancak malzemelerin uzaması üzerinde çok az etkisi görülmüştür. İş mili hızı, güç ve her iki malzemenin ortalama tane boyutu en az etkiye sahip olduğu görülmüştür. Ayrıca, hafif bir artış AA5754 uzama miktarında görülmüştür. Yağlayıcı etkisini incelemek için, hidrolik yağ ve gres, şekillendirme sırasında kullanılmıştır. Sonuçlar göstermektedir ki, hidrolik yağı kullanımı ile parça sağlamlığı artmaktadır, ancak, gres yağı ile oluşturulan parçalarda ortalama tane büyüklüğünün arttığı görülmektedir. Sonuçlardan yola çıkıldığında, duvar açısı ve besleme oranı, SPIF işleminde mikroyapı ve mekanik özelliklerde en önemli parametrelerdir. Anahtar Kelimeler: Tek Noktalı Artan Şekillendirme, Mekanik özellikler, mikroyapılar, duvar açısı, besleme oranı, Mil hızı, yağlayıcı madde, çekme Testi, AA5754, AA6061
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2014. Supervisor: Assist. Prof. Dr. Ghulam Hussain.
Keywords: Mechanical Engineering; Mechanical Properties; Single Point Incremental Forming; Microstructures; Wall angle; Feed rate; Spindle speed; Lubricant; Tensile test; AA6061; AA5754